The Effect of Buscopan((R)) on the Development of the Blow Fly Chrysomya megacephala (F.) (Diptera: Calliphoridae) - Oliveira, Helena G. [UNESP]; Gomes, Guilherme [UNESP]; Morlin, Jose J. [UNESP]; Von Zuben, Claudio J. [UNESP]; Linhares, Aricio X. (Wiley-Blackwell Publishing, Inc, 2009)
This work investigated the effects of butylscopolamine bromide, a drug present in the pharmaceutical formulation Buscopan((R)), on the development of Chrysomya megacephala, a blow fly species of considerable forensic and medical importance in Brazil. Larvae exposed to the drug showed a decreased rate of development, with higher drug concentrations further retarding the development. Besides, larvae reared on the presence of the drug showed smaller body weight and body length when compared with larvae reared on the absence of Buscopan((R)). The drug also affected the mortality of the species.
Keywords: forensic science; Chrysomya megacephala; entomotoxicology; forensic entomology; butylscopolamine bromide